Proceedings of the 8th International Workshop on Chiral Dynamics — PoS(CD15) 2016
DOI: 10.22323/1.253.0123
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear electric dipole moment of light nuclei in the gaussian expansion method

Abstract: The nuclear electric dipole moment is a very sensitive probe of CP violation beyond the standard model, and for light nuclei, it can be evaluated accurately using few-body calculational methods. In this talk, we present the deuteron, 3 He, 3 H, 6 Li, and 9 Be electric dipole moments calculated using the Gaussian expansion method with a realistic nuclear force, and assuming the one-meson exchange model for the P, CP-odd nuclear force. We then give future prospects for models beyond the standard model such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…The SM model contribution to the quark EDM and chromo-EDM is induced at the three-loop level with a value of the order of d q ∼ 10 −35 e cm [40], being thus negligible. We have to note, however, that the long distance contribution at the hadronic level is three to four orders of magnitude larger [41][42][43][44][45], which is not "extremely" small, although it is still below the prospective expermental sensitivity.…”
Section: Prospects For New Physicsmentioning
confidence: 74%
“…The SM model contribution to the quark EDM and chromo-EDM is induced at the three-loop level with a value of the order of d q ∼ 10 −35 e cm [40], being thus negligible. We have to note, however, that the long distance contribution at the hadronic level is three to four orders of magnitude larger [41][42][43][44][45], which is not "extremely" small, although it is still below the prospective expermental sensitivity.…”
Section: Prospects For New Physicsmentioning
confidence: 74%
“…The next-to-next-to-leading logarithmic order evolution of the SM contribution enhances one of the penguin operator (see Fig. 2) by a factor of about 40 when the scale is varied from µ = mW to µ = 1 GeV [266,267,268]. This effect is nontrivial and enhances the SM contribution to the nucleon level CP-odd processes from the naive estimation.…”
Section: Rge Of Strong Cp-odd Operatorsmentioning
confidence: 91%
“…The CP-odd π-N-N coupling in SM ḡ(1) πNN,SM = O(10 −17 ) which was given in the factorization approach with the |∆S| = 1 four-quark interaction calculated obtained from the two-loop level renormailzation group evolution (see also the end of Sec. 3.3) [268]. The CP-odd e-N interaction generated by the exchange of the Higgs boson in the SM is negligibly small [388].…”
mentioning
confidence: 98%
“…As for the nucleon EDM, this contribution is larger than the quark EDM and chromo-EDM contributions by two or three orders of magnitude [48][49][50]. In the case of nuclear EDM or the nuclear Schiff moment, it was also shown that the long distance effect is also much larger than the short distance one [51][52][53]. Then what about the lepton EDM?…”
mentioning
confidence: 99%
“…For the case of the |∆S| = 1 four-quark interaction, the renormalization from the electroweak scale µ = m W to the hadronic scale µ = 1 GeV changes the Wilson coefficients z i . From the numerical calculation of the running in the next-to-next leading logarithmic approximation [51,56], we obtain…”
mentioning
confidence: 99%